Obesity and underweight in children who undergo catheterization for congenital heart disease: A retrospective study - Andriana Anagnostopoulou; Nikolaos Eleftherakis; Evangelos Karanasios (Elsevier, 2024)
Background: Τhe number of overweight and obesity in the pediatric population has increased dramatically, a trend that is followed by a corresponding increase in the pediatric population with congenital heart disease. Notwithstanding, children with congenital heart disease seem to follow abnormal growth patterns. The aim of the present study is to determine the prevalence of obesity and underweight in children who undergo cardiac catheterization. Methodology: This is a retrospective study conducted in the cardiac catheterization laboratory of a large pediatric hospitalin the years 2011-2019. The children's anthropometric data were collected and the body mass index was calculated, according to the Centers for Diseases Control and Prevention definition. The chi -square test was used to identify any associations between catheterization, heart disease, body habitus, sex and age groups, after which a one way analysis of variance was performed to investigate the effects of the above variables on obesity. Results: The participants included 378 children from 2 to19 years old who underwent cardiac catheterization in the years 2011-2019. Cumulatively, 18.7% of the children in the study were underweight, 54.76 % were normal weight, 11.64 % were overweight and 14.81 % were children classified as with obesity. Overall, 26.45 % of the children weighed more than the 85th centile. The Kolmogorov Smirnoff test was used to test form normality and only the height in cms had a normal distribution. Children with acyanotic heart disease had a median age of 8 years old (IQR 6 years). The percentages of underweight were 16.6 %, the ones with healthy weight 53.58 %, 12.08 % overweight and 17.47 % with obesity. Children with cyanotic heart disease had a median age of 6 years (IQR 6) while the respective percentages of underweight, healthy weight, overweight and with obesity were 27.7%, 56.63%, 9.05% and 6.02%. These differences were statistically significant. However, the children who underwent a catheterization for other causes had a median age of 8 years old (IQR 8) and their percentages of underweight were 13.3%, the ones with healthy weight 60% and the ones with overweight or obesity 13.3% each. Conclusions: There is a significant discrepancy in the rate of obesity between the children with acyanotic and cyanotic heart disease. However, the differences between the children with acyanotic heart disease and children who underwent cardiac catheterization for other causes is not statistically significant.